A New Conservative Difference Scheme for the General Rosenau-RLW Equation. (20th October 2010) - Zuo, Jin-Ming; Zhang, Yao-Ming; Zhang, Tian-De; Chang, Feng
Abstract : A new conservative finite difference scheme is presented for an initial-boundary value problem of the general Rosenau-RLW equation. Existence of its difference solutions are proved by Brouwer fixed point theorem. It is proved by the discrete energy method that the scheme is uniquely solvable, unconditionally stable, and second-order convergent. Numerical examples show the efficiency of the scheme.